Spatial and temporal analysis of childhoodblood lead levels across Kansas: 2006-2011 - Kenne, Gabriel (My University, 2013)
The negative developmental and behavioral effects of chronic low dose exposures to lead in children are being better understood as research technology advances. To monitor and prevent childhood exposures, the CDC recommends that states create their own targeted screening programs. Here we use data from STELLAR, a statewide childhood blood lead tracking program for the state of Kansas, to analyze spatial and temporal relationships in the distribution of child blood lead tests for the 6 year study period of 2006 to 2011. Nonspatial demographic data from STELLAR is also analyzed to identify potential demographic target zones such as race, ethnicity, or sex. Data from the database was analyzed in ArcGIS software by county or census tract along with the most recent available census data to understand both the spatial and nonspatial trends within the demographic data. Geographic mean blood lead levels were also calculated for Kansas counties and displayed spatially. A large quantity of missing or errant geographic (address) and demographic data within the STELLAR database, however, created a lack of confidence in observed trends and made it impossible to conclusively identify potential targeted screening regions. Higher quality data and consistent data entry at physician locations is necessary for spatial analyses such as these to provide conclusive evidence for future interventions and screening programs to prevent childhood lead poisoning and exposures.
Keywords: Lead levels in blood; Chronic lead exposuse; Public Health (0573)